Newton's Interpolation Methods: P. Sam Johnson
Newton's Interpolation Methods: P. Sam Johnson
Newton's Interpolation Methods: P. Sam Johnson
P. Sam Johnson
February 7, 2020
y = p(x)
passes through a finite set of given data points. The function p(x) is
known as the interpolating function or smoothing function.
(in thousands)
y = a0 + a1 x + · · · + an x n (an 6= 0).
Thus for the theory of interpolation, it is not esssential that the functional
form of f (x) be known. The only information needed is the values of the
function given for some values of the argument.
Weierstrass approximation
theorem is illustrated in the
figure.
There are no sudden jumps or falls in the values of the function from one
period to another. This assumption refers to the smoothness of f (x) i.e.,
the shape of the curve y = f (x) changes gradually over the period under
consideration.
For example, if the population figures are given for, 1931, 1951, 1961, 1971
and figures for 1941 are to be interpolated, we shall have to assume that
the year 1941 was not an exceptional year, such as that affected by
epidemics, war or other calamity or large scale immigration.
(xi , yi ), i = 0, 1, 2, . . . , n
pn (xi ) = yi
for i = 0, 1, 2, . . . , n.
where
πn+1 (x) = (x − x0 )(x − x1 ) · · · (x − xn )
and L is to be determined such that the equation (1) holds for any
intermediate value of x 0 ∈ (x0 , xn ). Clearly
y (x 0 ) − pn (x 0 )
L= . (2)
πn+1 (x 0 )
so that
y (n+1) (ξ)
L= . (4)
(n + 1)!
y (n+1) (ξ)
y (x 0 ) − pn (x 0 ) = πn+1 (x 0 ).
(n + 1)!
(x − x0 )(x − x1 ) · · · (x − xn ) (n+1)
y (x) − pn (x) = y (ξ) (5)
(n + 1)!
which is the required expression for the error. Since y (x) is, generally,
unknown and hence we do not have any information concerning y (n+1) (x),
formula (5) is almost useless in practical computations.
xi = x0 + ih, i = 0, 1, 2, . . . , n.
pn (x) = a0 +a1 (x −x0 )+a2 (x −x0 )(x −x1 )+· · ·+an (x −x0 )(x −x1 ) · · · (x −xn−1 ).
Imposing the condition that y and pn (x) should agree at the set of
tabulated points, we obtain
a0 = y0
y1 − y0 ∆y0
a1 = =
x1 − x0 h
∆2 y 0
a2 =
h2 2!
∆3 y 0
a3 =
h3 3!
..
.
∆n y0
an = .
hn n!
Therefore
∆y0 ∆2 y0
pn (x) = y0 + (x − x0 ) + 2 (x − x0 )(x − x1 ) + · · ·
h h 2!
∆n y0
··· + (x − x0 )(x − x1 ) · · · (x − xn−1 )
hn n!
is the polynomial of degree n agreeing with the (unknown) function y at
the tabulated points.
(x − x0 )(x − x1 ) · · · (x − xn ) (n+1)
f (x) − pn (x) = f (ξ),
(n + 1)!
The first two terms of Newton’s forward formula give the linear
interpolation while the first three terms give a parabolic interpolation
and so on.
1. Prove that
(a) y2 = y0 + 2∆y0 + ∆2 y0 .
(b) y3 = y0 + 3∆y0 + 3∆2 y0 + ∆3 y0 .
2. Show that h i
(a) ∆(tan−1 x) = tan−1 h
1+hx+x 2 .
h i
4h
(b) ∆ log(1 + 4x) = log 1 + 1+4x .
3. Evaluate
(a) ∆3 (1 − x)(1 − 2x)(1 − 3x) if h = 1.
(b) ∆10 (1 − x)(1 − 2x)(1 − 3x) . . . (1 − 10x) taking h = 1.
(c) ∆10 [(1 − x)(1 − 2x 2 )(1 − 3x 3 )(1 − 4x 4 )] if h = 2.
(d) ∆10 [(1 − ax)(1 − bx 2 )(1 − cx 3 )(1 − dx 4 )].
1. Prove that
(a) (∆ − ∇)f (x) = ∆∇f (x).
(b) ∆∇ and ∆ − ∇ are equal operators. That is, ∆∇ = ∆ − ∇.
2. Prove that ∆[f (x − 1)∆g (x − 1)] = ∇[f (x)∆g (x)].
[ Hint : ∆[f (x) g (x)] = f (x) ∆g (x) + g (x + h) ∆f (x). ]
Let us recall the following expression for the first forward difference of a
function f (x) for equally spaced values of x with step-length h:
∆f (x) = f (x + h) − f (x).
f (x + h) = f (x) + ∆f (x)
= (1 + ∆)f (x).
E =1+∆
Ef (x) = f (x + h).
E n f (x) = f (x + nh), n = 1, 2, 3, . . . .
E n is called the nth order shift order as it shifts the value of the function at
x to the value at x + nh. We can write the formula in an alternative form:
E n ym = ym+n .
P. Sam Johnson (NITK) Newton’s Interpolation Methods February 7, 2020 27 / 47
Shift Operator
Exercise 5.
Let the function y = f (x) take the values y0 , y1 , . . . , yn corresponding to
the values x0 , x0 + h, . . . , x0 + nh of x. Suppose f (x) is a polynomial of
degree n and it is required to evaluate f (x) for x = x0 + ph, where p is a
any real number. Derive Newton’s forward difference interpolation
formula, by using shift operator E .
[ Hint : yp = f (x) = f (x0 + ph) = E p f (x0 ) = (1 + ∆)p y0 . ]
1. Evaluate
(a) E (x 2 − 3x + 1).
(b) (E 2 + 1)(x 3 + 2x 2 − 5x).
(c) E −1 (x 5 − x 3 + 1).
(d) E −3 (x 7 + x 5 + x 3 + x + 1).
2. Evaluate
(a) E 3 e x and then E n e x , where x varies by a constant interval h.
(b) (E − 1)(E − 2)x.
(c) (E − 3)(E + 4)3x .
(d) (E + 2)(E − 1)(2x/h + x).
3. Expand the following :
(a) (2E − 3)(5∆ + 4)x 2 .
(b) ∆2 E −3 x 5 and prove that ∆3 y3 = ∆3 y6 .
∆2 ∆2 sin(x+h)
1. Evaluate E sin(x + h) + E sin(x+h) .
2. Estimate the missing term in the following table :
x 0 1 2 3 4
y=f(x) 1 2 6 ? 51
3. If u0 = 5, u1 = 11, u2 = 22, u3 = 40, u5 = 140, then find u4 , given
that the general term is represented by a fourth-degree polynomial.
4. Find log710 and log11 x
10 from the data given f (x) = log10 for some values
of x.
x 6 7 8 9 10 11 12
f (x) = logx10 0.77815 ? 0.90309 0.95424 1.0000 ? 1.07918
[Hint : 5 values of x and the corresponding values of y = f (x) are given, so ∆5 f (x) = 0,
for all x. By taking x as x0 and x1 , we get two expressions in y0 , y1 , . . . , y6 .]
(x − x0 )(x − x1 ) . . . (x − xn ) (n+1)
y (x) − pn (x) = y (ξ)
(n + 1)!
Neverthless, if y (n+1) (x) does not vary too rapidly in the interval, a useful
estimate of the derivative can be obtained in the following way. Expanding
y (x + h) by Taylor’s series, we obtain
h2 00
y (x + h) = y (x) + hy 0 (x) + y (x) + · · · .
2!
Neglecting the terms containing h2 and higher powers of h, this gives
y (x + h) − y (x) ∆y (x)
y 0 (x) ≈ =
h h
· · · + an (x − xn )(x − xn−1 ) · · · (x − x1 )
and then impose the condition that y and pn (x) should agree at the
tabulated points xn , xn−1 , . . . , x2 , x1 , x0 , we obtain (after some
simplification)
p(p + 1) 2 p(p + 1) · · · (p + n − 1) n
pn (x) = yn + p∇yn + ∇ yn + · · · + ∇ yn
2! n!
where p = (x − xn )/h.
and
(x − x0 )n+1 (n+1)
Rn (x) = f (ξ) (error term)
(n + 1)!
for some ξ between x and x0 .
Hence “ξ between x and x0 ” means that either x0 < ξ < x or x < ξ < x0
depending on the particular values of x and x0 involved.
Taylor’s theorem simply ensures that such a function exists, and that its
value lies between x and x0 .
n 0 1 2 3 4 5 6 7
pn (3) 1 -1 3 -5 11 -21 43 -85
Since the Taylor polynomials have the property that all the information
used in the approximation is concentrated at the single point x0 , it is not
uncommon for these polynomials to give inaccurate approximations as we
move away from x0 . This limits Taylor polynomial approximation to the
situation in which approximations are needed only at points close to x0 .
The following formulae are based on central differences which are best
suited for interpolation near the middle of the table.
The coefficients in the above central difference formulae are smaller and
converge faster than those in Newton’s formulae.
P. Sam Johnson (NITK) Newton’s Interpolation Methods February 7, 2020 46 / 47
References